STRATEGI PENGEMBANGAN POTENSI TAMAN MAYURA SEBAGAI PUSAT REKREASI DI KOTA MATARAM - ida Bagus Dimasoka; Siluh Putu Damayanti; I Gede widya suputra; Indrapati Indrapati (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
Abstract: The problems studied in this study are related to the potential development of Mayura Park as a recreation center in Mataram City with the aim of describing how the development strategy in Mayura Park is. The research method used is a qualitative approach. Data collection techniques in the form of interviews, observations, and documentation with informants, namely managers and visitors of Mayura Park. The data will be processed using a SWOT matrix analysis to formulate an appropriate Mayura Park development strategy. The results showed that Mayura Park has various potentials that can be seen from the 4A side. Such as: the attraction of three historic buildings, adequate road accessibility, adequate garden facilities, and ancillary services available in the form of ATM, BANK, gas stations, and Money Changers. Meanwhile, the SWOT factors found data on internal factors that Mayura Park has strengths in the park's uniqueness, facilities and high visitation rates on weekends. The weakness lies in the management system, infrastructure that has not been maximized, the absence of zoning, and lack of promotion. Meanwhile, on external factors, it was found that the opportunity for Mayura Park lies in a location that is in the center of the economy and tourist route. Threats from Mayura Park are the lack of permanent financial support from the government, the number of visits that tends to stagnate, and competition between destinations. The results of the SWOT matrix analysis were combined and created 4 strategies, namely: a strategy for developing the potential attractiveness of Mayura Park as a recreational park (SO), a strategy for developing recreational park tourism infrastructure (WO), a managerial and financial improvement strategy (ST), and a strategy for developing a tourism infrastructure sustainable tourism planning and development (WT).